RECOGNITION OF THE MEDITERRANEAN FLY Ceratitis capitata (Wiedemann) (DIPTERA: TEPHRITIDAE) IN THE DEPARTMENT OF NARIÑO - COBO DE MARTÍNEZ, LUZ STELLA; VIDAL, GLORIA; NÚÑEZ-BUENO, LIGIA (Revista Colombiana de Entomología, 1989)
The Mediterranean fruit fly Ceratitis capitata, was detected by the first time in Colombia, in September 1986. The first males were captured in Nariño, closed to the border with Ecuador. Jackson traps with, Trimedlure were sep up in all the coffee and fruit growing areas with the objective to establish the distribution. Fruit samples were analyzed to determine the main hosts. Two infested areas were determined between February-march 1987. The first (10.000 ha) close to the Guaitara’s river coffee-growing areas (t. 1719°C; -1.400-1900 m.a.s.I.). The second (400 ha), in the north-west part of the Nariño Department, is located in the urban area of San Pablo (t. 19°C; 1700-1750 m.c.s.I.). The pest was introduced in infested fruits from Ecuador to a populated zone situated 20 km. north of the border, from that initial infested area it has been naturally dispersed and/or transported by man to other areas. It will be possible for the medfly to establish in all the fruit growing areas of Nariño, due to temperature condition diversion and continuous presence of available hosts coffee barries were only one host reported at this time.